Urban subjectivities in crisis: A study of three novels by Carmen Naranjo Coto (1966-1968) - Cubillo Paniagua, Ruth (2022)
The Costa Rican writer Carmen Naranjo Coto (1928-2012) makes, in her early novels, published in the 1960s, a profound reflection related to the city of San José and its residents, who face processes of coexistence in the context of a Central American capital that begins its entry into globalization. To demonstrate this, the next novels are analyzed Los perros no ladraron (1966); Camino al mediodía (1968) and Memorias de un hombre palabra (1968), whose characters are subjects with their own concerns about the transition from modernity to postmodernity, since what is in crisis is the very construction of subjectivity and the questioning of the absolute truths. As thematic axes of the analysis, indifference as a generator of anguish in the subject and the invisibility of the subject-citizen are proposed. Also, a dialogue is established between Naranjo's novels and some of the conceptual proposals of authors such as the philosopher and sociologist Georg Simmel, the psychoanalyst Sigmund Freud, the philosopher and sociologist Herbert Marcuse, and the literary critic Rafael Valenzuela.